Clinical Assessment of the Autonomic Nervous System - Iwase, Satoshi; Hayano, Junichiro; Orimo, Satoshi (Springer Japan : Imprint: Springer, 2017)
This book describes newly developed methods of assessing the autonomic nervous system. Up-to-date information on microneurographic analysis of human cardiovascular and thermoregulatory function in humans, heart rate variability, and131I-metaiodobenzylguanidine (MIBG) scintigraphy are provided. Microneurography, which was originally developed as a technique to analyze the afferent muscle spindle, came to be used to analyze sympathetic nerve activity in the mid-1980s. In the twenty-first century, this technique has become prevalent all over the world especially in investigating the pathophysiology of human cardiovascular function. It is also now used in researching human thermoregulatory function. Heart rate variability is another valuable tool in investigating the current status of human vagal function and in predicting future cardiovascular disease. MIBG is also used to assess cardiac noradrenergic function, especially decreases associated with Parkinson's disease, Lewy body disease, and multisystem atrophy. Overviews of recent advances in these three important assessments are provided by leading experts. Clinical Assessment of the Autonomic Nervous System is a useful resource for neurologists and researchers of clinical neurophysiology.
Keywords: Medicine.; Human physiology.; Neurosciences.; Neurology.; elektronické knihy; electronic books